Die Puppen der mitteleuropäischen Argyresthiinae (Lepidoptera, Yponomeutoidea, Yponomeutidae). - Patočka, Jan (Contributions to Entomology = Beiträge zur Entomologie, 1998)
The pupae of genus Argyresthia with 23 species of Central European Argyresthiinae (Lepidoptera, Yponomeutoidea, Yponomeutidae) are characterized, described and figured and a key for the identification of species as well as some data on the biology and habitats are added. The present system of this group is discussed on the basis of pupal characters. Keywords Lepidoptera, Yponomeutidae, Argyresthiinae, Central Europe, pupae, external morphology, key, taxonomy, bionomics.